Three-dimensional bioprinting of aneurysm-bearing tissue structure for endovascular deployment of embolization coils. (16th October 2020) - Jang, Lindy K; Alvarado, Javier A; Pepona, Marianna; Wasson, Elisa M; Nash, Landon D; Ortega, Jason M; Randles, Amanda; Maitland, Duncan J; Moya, Monica L; Hynes, William F
Abstract: Various types of embolization devices have been developed for the treatment of cerebral aneurysms. However, it is challenging to properly evaluate device performance and train medical personnel for device deployment without the aid of functionally relevant models. Current in vitro aneurysm models suffer from a lack of key functional and morphological features of brain vasculature that limit their applicability for these purposes. These features include the physiologically relevant mechanical properties and the dynamic cellular environment of blood vessels subjected to constant fluid flow. Herein, we developed three-dimensionally (3D) printed aneurysm-bearing vascularized tissue structures using gelatin-fibrin hydrogel of which the inner vessel walls were seeded with human cerebral microvascular endothelial cells (hCMECs). The hCMECs readily exhibited cellular attachment, spreading, and confluency all around the vessel walls, including the aneurysm walls. Additionally, the in vitro platform was directly amenable to flow measurements via particle image velocimetry, enabling the direct assessment of the vascular flow dynamics for comparison to a 3D computational fluid dynamics model. Detachable coils were delivered into the printed aneurysm sac through the vessel using a microcatheter and static blood plasma clotting was monitored inside the aneurysm sac and around the coils. This biomimetic in vitro aneurysm model is a promising method for examining the biocompatibility and hemostatic efficiency of embolization devices and for providing hemodynamic information which would aid in predicting aneurysm rupture or healing response after treatment.